STRATEGI PEMASARAN KERAJINAN TENUN IKAT SUMBA SEBAGAI PRODUK INDUSTRI KREATIF PENDUKUNG PARIWISATA DI SUMBA TIMUR - Hanja, Hendrina Mbitu; Sasrawan Mananda, I GPB.; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
This research refers to Sumba ikat weaving crafts as a creative industry product in East Sumba, a case study at one of the souvenir shops namely Artshop Maradda Indah. This study aims to find out the strategy of Artshop Maradda Indah in marketing Sumba ikat weaving crafts as a creative industry product in East Sumba and look for new strategies based on existing strengths, weaknesses, opportunities, and threats. The sample determination technique uses accidental sampling technique by distributing internal environment questionnaires to 130 customers at Artshop Maradda Indah. Respondents to answer external indicators were determined by the quota sampling technique, namely as many as 10 respondents using the likert scale technique. Data analysis techniques using IFAS & EFAS analysis methods, IE matrix analysis and SWOT analysis. The results based on the dissemination of the internal questionnaire, 8 strengths and 4 weaknesses were obtained with an IFAS score of 2.87 and 9 opportunities and 5 threats with an EFAS score of 2.85 from the distribution of the external environment questionnaire. Thus, it can be known that Artshop Maradda Indah is in cell V on the IE matrix with a strategy that can be applied of is a growth and stability strategy.